Management of Root Perforation : A Case Report - Sylvia Paulina Panggono; Teuku Chairil Hafiz; Tamara Yuanita (Conservative Dentistry Journal, 2022)
Background : Root perforation results in the communication between root canal walls and periodontal space (external tooth surface). It is commonly caused by an operative procedural accident or pathological alteration (such as extensive dental caries, and external or internal inflammatory root resorption). The diagnosis of dental pulp and/or periapical tissue previous to root perforation is an important predictor of prognosis. Case : A female patient came to Dental Conservative University of Airlangga with complaints of perforated lower left molars. On the objective examination obtained negative vitality test, positive on bite test. On radiographic examination, a radiolucent on bifurcation was performed Case management : The tooth was treated by hemisection. Root canal treatment was carried out in the distal canals. Afterwards, the tooth was split mesio-distally. The mesial root was extracted, and the distal root was retained and restored with PFM Crown. Discussion : Hemisection is a useful alternative treatment to extraction to save the multi-rooted teeth by endodontic approach, which includes the root canal treatment of the remaining roots and restoring them with suitable restorative material to splinting it with the adjacent tooth to decrease the risk of displacement followed by a fixed prosthodontic prosthesis to maintain the occlusal balance. Conclusion : Hemisection with subsequent prosthetic rehabilitation can be a viable alternative to retain severely decayed mandibular molar.